Penyusunan Anggaran Pendapatan dan Belanja Desa Lampung Tengah - Vinanda, Olivia Rizka (IAI Nasional Laa Roiba Bogor, 2024)
With the issuance of Law No. 6/2014 on Villages, the position of the village government has become stronger, because it is no longer regulated in Law No. 23/2014 on Regional Government, but is regulated by a separate law. In addition to strengthening the status of the village as a community government, the Village Law also makes the village the basis for advancing the community and empowering the village community. Villages have the right to autonomy. As a logical consequence of having autonomy, it must have its own finances. Article 93 of Government Regulation No. 43/2014 on the Implementation of Law No. 6/2014 on Villages states that village finances include planning, implementation, administration, reporting, and accountability. Article 101 of Government Regulation No. 43/2014 on the Implementation of Law No. 6/2014 on Villages mentions the mechanism for preparing the Village Budget. The research method used in this research is a normative juridical approach. The results showed that the mechanism for preparing the Village Budget of Central Lampung Regency as the implementation of Article 101 of Government Regulation Number 43 of 2014 concerning the Implementation Regulations of Law Number 6 of 2014 concerning Villages has been implemented based on Article 20 of the Regulation of the Regent of Central Lampung Regency Number 14 of 2015 concerning Village Financial Management in Central Lampung Regency through 3 (three) stages, namely the preparation, evaluation and determination stages. Supporting factors in the preparation of the Revenue and Expenditure Budget are the existence of assistants in the preparation of the Revenue and Expenditure Budget from the District and Regency, the government facilitates with the training of Village Heads and Village Apparatus every 3 (three) months at the provincial level and at the district level, and inhibiting factors in the preparation of the Village Revenue and Expenditure Budget, namely because Law Number 6 of 2014 and its implementing regulations are still new so that the community is not used to it and results in difficulty socializing with the community in village meetings.